Conversion Fails in Indonesian Higher Education from Application to Enrolment Uncovering Why Applicant - Nana Noviada Kwartawaty; Mohd Hasmadi Ismail; Achmad Solechan (Universitas Palan, 2026)
This study investigates why applicants who have passed the initial admissions stage do not proceed to final enrolment in an Indonesian private higher education context. While student recruitment is often measured by the number of applications received, institutional sustainability depends on the ability to convert applicants into enrolled students. This study employed a descriptive survey design supported by thematic analysis of open-ended responses. Data were collected from 179 applicants who had participated in the admissions process but did not complete final re-registration. The data were analyzed using frequencies, percentages, and thematic categorization. The findings show that conversion failure is influenced by several factors, including waiting for public university admission results, financial constraints, postponement of study plans, family considerations, uncertainty about the institution or study programmed, preference for other institutions, and campus accessibility. A key finding reveals that 58.1% of respondents would reconsider enrolment if scholarships, tuition discounts, or other financial assistance were available. These findings highlight the need for a conversion management strategy through targeted financial aid, transparent cost communication, family engagement, and proactive applicant follow-up.